2015
DOI: 10.1093/czoolo/61.6.1036
|View full text |Cite
|
Sign up to set email alerts
|

Male Drosophila melanogaster learn to prefer an arbitrary trait associated with female mating status

Abstract: Although males are generally less discriminating than females when it comes to choosing a mate, they still benefit from distinguishing between mates that are receptive to courtship and those that are not, in order to avoid wasting time and energy. It is known that males of Drosophila melanogaster are able to learn to associate olfactory and gustatory cues with female receptivity, but the role of more arbitrary, visual cues in mate choice learning has been overlooked to date in this species. We therefore carrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…No such significant change in courtship behaviour was observed for males interacting with a Small female, while males interacting with Control females reduced their CP somewhat. Our results add to the growing literature demonstrating that male D. melanogaster can associate a variety of female phenotypic traits with prior courtship failure and subsequently learn to reduce courtship behaviour towards females with those particular traits (Dukas, , ; Ejima et al., , ; Griffith & Ejima, ; Mehren, Ejima, & Griffith, ; Verzijden et al., ).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…No such significant change in courtship behaviour was observed for males interacting with a Small female, while males interacting with Control females reduced their CP somewhat. Our results add to the growing literature demonstrating that male D. melanogaster can associate a variety of female phenotypic traits with prior courtship failure and subsequently learn to reduce courtship behaviour towards females with those particular traits (Dukas, , ; Ejima et al., , ; Griffith & Ejima, ; Mehren, Ejima, & Griffith, ; Verzijden et al., ).…”
Section: Discussionsupporting
confidence: 71%
“…Courtship learning occurs when males modify their courtship behaviour following experience (Griffith & Ejima, ; Siegel & Hall, ; Verzijden, Abbott, Philipsborn, & Loeschcke, ). Male Drosophila melanogaster exhibits courtship learning with regard to non‐receptive females, which includes both sexually immature and recently mated females (Rezával et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Experienced female damselflies learn to reject heterospecific males by recognizing their wing patches (Svensson et al, 2010(Svensson et al, , 2014Verzijden and Svensson, 2016). The acquisition of a preference for visual traits has also been reported in fruit flies [eye color, (Verzijden et al, 2015)], butterflies [hindwing ornamentation number, (Westerman et al, 2014)], or crickets [size, (Bateman et al, 2001)] (Figure 2). Recent studies on matechoice copying showed that virgin individuals tend to prefer male phenotypes with similar color type and ornamentation as the mate choice of another conspecific, e.g., in spiders, (Fowler-Finn et al, 2015) and fruit flies, (Mery et al, 2009;Nöbel et al, 2018a).…”
Section: Visual Signalsmentioning
confidence: 78%
“…Recent results suggest that vision may be more important to mating in Drosophila than was previously expected (Ribeiro et al 2018). Similarly, learned male mate choice has been demonstrated in the ancestral population (Verzijden et al 2015), and it is known that males use memory to evaluate their risk of sperm competition and allocate resources accordingly (Rouse et al 2018), so terms related to learning, memory and nervous system development may also be a result of selection via mating interactions.…”
Section: Genomic Location and Function Of Genes That Changed In Exprementioning
confidence: 88%